Older people as models in advertisements: A cross-cultural content analysis of two Asian countries - Fon, S.O.; Kitchen, P.J. (2008)
The purpose of this paper is to investigate the extent to which older people are used as models in television advertisements in Korea and Malaysia, representing an aged and ageing nation, respectively. The paper examines the roles and functions played by older people in advertisements that portray these older people as models; and the social context, setting and tone of advertisements. Television advertisements from major television channels in Korea and Malaysia were recorded during prime time. These recordings were coded by two experts in each country. Data were analyzed using content analysis. The findings show that older people are underrepresented compared to their proportion in both countries. Older males are overly represented while older females are underrepresented, in both countries. Overall, older people were portrayed in a positive way even though they tended to play minor roles. However, regardless of gender, they are invarably cast as information receivers rather than senders.